A factor from neurons increases the number of acetylcholine receptor aggregates on cultured muscle cells. - Christian, C N (1978)
There is an increase in the number of acetylcholine (AcCho) receptor aggregates on striated embryonic mouse myotubules when they are cocultured with clonal neuroblastoma-glioma hybrid cells. Medium conditioned by hybrid cells contains a factor which increases the number of AcCho receptor aggregates on myotubes cultured from mouse, rat or chick muscle. AcCho receptor-aggregating activity was present in medium conditioned by the neuroblastoma parent clone but was not detected in medium conditioned by cells of the parent glioma clone, fibroblasts, or HeLa cells. The factor increased the aggregation of AcCho receptors within 24 hr without a significant increase in the total number of AcCho receptors, and its action did not depend on myotube protein synthesis. The factor appears to rearrange the distribution of myotube AcCho receptors either by aggregating mobile AcCho receptors or by stabilizing labile receptor aggregates.